Studi Ekploratif tentang Akuntabilitas Crowdfunding Wakaf - Santika, Dita; Ihsan, Hidayatul; Eliyanora, Eliyanora; Gustina, Gustina (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to portray the mechanism of waqf crowdfunding and as to how crowdfunding operator and nazhirs (waqf managers) show their accountability to the public. In doing so, an exploratory study at kitabisa.com, one of the largest donation-based crowdfunding platforms in Indonesia, was conducted. Data was collected through interviews, email correspondences, and web content analysis while data analysis was conducted through thematic analysis. The findings of this study show that there have been some efforts made by both crowdfunding operator and nazhirs to discharge their accountability to the public. Meanwhile, the absence of existing regulation to waqf crowdfunding in Indonesia could be a threat to waqf accountability. This study concludes with recommendations for the improvement of waqf crowdfunding in the future.